Relationship between tremor and the onset of rapid voluntary contraction in Parkinson's disease. Issue 7 (July 1993) - Wierzbicka, M M; Staude, G; Wolf, W; Dengler, R
Abstract : It has been suggested that initiation of voluntary movement in Parkinson's disease (PD) is synchronous with tremor beats. This hypothesis was tested by examining quantitatively the onset of voluntary contraction in relation to the tremor cycle. Five PD patients with tremor at rest produced fast isometric abduction of the index finger in reaction time and self-paced trials. For each trial, the time interval from last tremor peak to contraction onset was evaluated and its frequency distribution was compared with proposed statistical models. It was found that patients most often initiated contractions during the descending phase of the tremor oscillation and that the phasic EMG burst most commonly occurred after the mid-point of the EMG tremor cycle in both self-paced and reaction time conditions. These results indicate that voluntary contraction is not initiated arbitrarily with respect to the tremor oscillation. Rather, there is a systematic phase relationship between the onset of the voluntary response and tremor. Thus attraction of voluntary movement to the tremor oscillator in PD results from abnormally synchronised motor units and failure to activate the motor neuron pool voluntarily soon after the tremor discharge.